Mobilisation identitaire et représentation politique des « Turcs » en Thrace occidentale : les élections législatives grecques de mars 2004 - Jeanne Hersant; Nepheli Yatropoulos (European Journal of Turkish Studies)
Western Thrace is a Greek region bordering Bulgaria and Turkey. Two of its administrative divisions (nomos) – Rhodopi and Xanthi – are mainly inhabited by members of the so-called ‘Muslim minority’. Muslims remained in Greece after the 1924 compulsory population exchange with Turkey. Most of them are Turkish speakers and their electoral momentum has implications on the resonance of their political leaders’ demand concerning the recognition by the Greek state of their ‘Turkishness’. Since the beginning of the year 2000, in a context of European integration, claims linked to the ‘Turkish’ identity of the minority have been considered legitimate in the local political field, and are even taken over by some local ‘Christian’ politicians during electoral campaigns. These claims are still officially considered, however, as an element of national divide and consistently denounced in the courts by Greek state authorities. Despite the fact that both ‘Greek’ and ‘Turkish’ candidates suggest that voters have to vote along ethnic lines, the proportion of Muslim voters, that may theoretically allow the election of three ‘Turkish’ MPs, only one of them was elected in 2004. And yet, the electoral results show a proportionate increase in the votes for the ‘Turkish’ candidates. We have constituted a representative sample of the Muslim electorate in each nomos and made hypotheses in order to try to understand such a situation. These hypotheses deal with, on the one hand, the running rules of the local political field and the role of the ‘Turkish’ discourse in these rules; on the other hand, the Greek voting system’s specificities.